Perancangan Dan Pembuatan Struktur Rangka Dinamik Sun Tracking - Muhamad Rifan; Adhy Prayitno; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Riau is an area located on the equator, meaning that this region has the potential to be traversed by the sun throughout the year. This solar potential is an alternative to the use of energy derived from fossil energy. In general, solar cells are not optimal in the absorption of sunlight. Therefore, in this study designed a Sun Tracking engine that is destined for solar cell follow the movement of the sun. Stages of design consists of needs analysis, preparation of product technical specifications, designing product concepts to generate alternative product concepts which then selected the concept to be made. From the selection of concept is made the static analysis on the mechanical components of the Sun Tracking machine, which includes stress and deformation due to loading and own weight. The static analysis is done in two ways that is by manual calculation and finite element analysis using Autodesk Inventor 2012 Student Edition software. Based on the result of static analysis , revealed stress of 8.381 MPa on stem 1, 8.769 MPa on stem 2, 0.5378 MPa at stem 3 and 0.562 MPa on stem 4. Deformation happened is 0.026830 mm in stem 1 , 0.028073 mm on the stem 2, 0.0006277 mm on the trunk 3 and 0.0005041 mm on the trunk 4Keywords : Sun Tracking, Autodesk Inventor, Solar cell